EFFECT OF TRAINING AND CAREER DEVELOPMENT ON PERFORMANCE CIVIL SERVICES REGIONAL SECRETARIAT - Ari Hashari, Ari Hashari; Nadeak, Banuara; Chaerudin, Chaerudin (Jurnal Sosial Humaniora, 2022)
The purpose of this research is to ascertain whether training increases worker productivity or not, whether career development increases productivity or not, and whether both increase productivity or not. This research makes use of descriptive and corroborative methodologies. 106 people from the Karawang County Regional Secretariat took part in this research. Use online surveys to collect data. Multiple linear regression analysis, correlation analysis, the coefficient of determination, and hypothesis testing are all examples of traditional statistical approaches. The data was analyzed with SPSS 16, a statistical program. This study found a simple one-way relationship (correlation coefficient 39.4%) between training and job development factors. In the t-test for the partial regression coefficient, both the t-count of the training variable (6.345) and the t-count of career development (2.992) are greater than the t-table value of 1.983 and sig < (0.05). Meanwhile, according to the results of simultaneous regression coefficient testing (f test) obtained t count (37.963) > f table (3.08). Training and advancement opportunities have a total impact on employee performance by 42.4%, while other variables (ɛ) not examined in this study reached the remaining 57.6%.